A Case of Laparoscopic Mesenteric Cyst Excision - Vikalp Jain; Jonas P. DeMuro; Matthew Geller; Elena Selbs; Carlos Romero (Case Reports in Surgery)
The objective of this study is to discuss the presentation, diagnosis, and surgical management of a young, healthy patient with a symptomatic mesenteric cyst. He had a 5-month history of abdominal pain from this disorder, and the case is presented to illustrate the clinical picture and operative management of this rare disorder.